2021
DOI: 10.2169/internalmedicine.6520-20
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid-induced Immune Thrombocytopenia

Abstract: Drug-induced thrombocytopenia occurs through immune-mediated platelet destruction, and its management is challenging during tuberculosis treatment. Although rifampicin is the most common drug causing thrombocytopenia, isoniazid can also cause thrombocytopenia. We herein report a 75-year-old man who developed thrombocytopenia during tuberculosis treatment. Platelet-associated immunoglobulin G and a drug-induced lymphocyte stimulation test for isoniazid were positive; no other causes of thrombocytopenia were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Kuwabara et al found that isoniazid also causes immune thrombocytopenia by complement activation [ 10 ]. The bronchial clot, in this case, was a consequence of the vocal cord bleed, as the blood was continuously aspirated into the bronchus and formed a clot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kuwabara et al found that isoniazid also causes immune thrombocytopenia by complement activation [ 10 ]. The bronchial clot, in this case, was a consequence of the vocal cord bleed, as the blood was continuously aspirated into the bronchus and formed a clot.…”
Section: Discussionmentioning
confidence: 99%
“…This case illustrates how ATT can cause severe thrombocytopenia, which can lead to bleeding or bleeding tendencies. There are other side effects of ATT, which need timely monitoring, which include ethambutol-induced optic neuropathy, alteration in liver enzymes, chronic active hepatitis, acute hepatitis, acute kidney injury, aplastic anemia, and peripheral neuropathy [ 10 ]. This case highlights the importance of considering different causes of hemoptysis and hematemesis, and of conducting a comprehensive airway assessment in such patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…În cazul dat la pacient s-a dezvoltat o trombocitopenie acută și severă, în pofida absenței expunerii anterioare la R. Au fost raportate cazuri de trombocitopenie severă precoce, după expunerea inițială cu un debut până la 4-14 zile, care pot fi determinat și de factorii genetici sau de mediu predispozanți. Numărul de trombocite revine în decurs de o săptămână după întreruperea expunerii la preparatul sensibilizant, iar cazurile severe pot fi necesare alte tratamente, inclusiv glucocorticizi și imunoglobuline intravenos [6,8].…”
Section: Rezultate Și Discuțiiunclassified
“…Therefore, LZD was changed to intravenous TZD, an oxazolidinone similar to LZD but not known to cause thrombocytopenia [ 5 , 6 ]. In addition, intravenous administration of INH was also suggested as the cause of thrombocytopenia [ 7 ], and it was changed to intramuscular administration of SM 300 mg twice/week. The patient’s condition remained stable; his platelet count increased to 167×10 3 /µL, and serum C-reactive protein decreased to 1.41 mg/dL.…”
Section: Case Reportmentioning
confidence: 99%